Application of NanoScope in Treating Severe Shoulder Dysplasia With Intraarticular Osseous Bodies in a Cat - Julian Hauer; Barbara Bockstahler; Carina Strohmayer; Sabine Breit; Barbara Richter; Eva Schnabl‐Feichter (Veterinary Medicine and Science)
ABSTRACT Case summary A 2‐year and 9‐month‐old male neutered Himalayan cat was evaluated for lameness of the left thoracic limb. Orthopaedic examination and radiography revealed severe bilateral shoulder joint dysplasia and intraarticular osseous bodies. The lameness was resolved after successful removal of two intraarticular bodies from the left shoulder joint using a needle‐sized chip‐on‐tip technology arthroscope (NanoScope). Histology of these two bodies showed enchondral ossification. Nine months after surgery, radiographs showed a new osseous body at the same location as before, and a gait analysis using a pressure plate revealed mild lameness, which was not detectable in orthopaedic examination.